Apatite formation on a hydrogel containing sulfinic acid group under physiological conditions. Issue 7 (10th June 2016) - Hamai, Ryo; Shirosaki, Yuki; Miyazaki, Toshiki
Abstract: Natural bone consists of apatite and collagen fiber. Bioactive materials capable to bonding to bone tissue are clinically used as bone‐repairing materials. Apatite‐organic polymer composites exhibit bone‐bonding abilities and mechanical properties similar to those of natural bone, and these materials can be prepared using biomimetic processes in simulated body fluid (SBF). Specific functional groups such as sulfonic and carboxylic acid groups are known to induce the heterogeneous nucleation of apatite in SBF. However, it remains unclear whether structurally related sulfinic acid groups can contribute to apatite formation in the same way, despite sodium sulfonate being used in biomedical applications as a radical polymerization promoter in adhesive dental resin. Herein, we report the preparation of a new hydrogel containing sulfinic acid groups from sodium 4‐vinylbenzenesulfinate and 2‐hydroxyethyl methacrylate using a radical polymerization reaction and the subsequent incorporation of Ca 2+ ions into this material. We also investigated the apatite‐forming behavior of these hydrogels in SBF. Hydrogels containing sulfinic acid groups showed higher apatite‐forming ability than those without sulfinic acid groups. In addition, the apatite layer formed on the former showed tight adhesion to the hydrogel. This phenomenon was attributed to the heterogeneous nucleation of apatite, induced by the sulfinic acid groups. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 1924–1929, 2017.